(untitled) (Veterinary Science, 2021)
An exhaustive bibliographic search was carried out on epidemiology, surveillance and control strategies for Rabies variant 4 transmitted by insectivorous bats. Likewise, as a case study, a retrospective study of insectivorous bats captured by passive surveillance and analyzed to determine the presence of rabies virus was carried out in the Province of Río Negro, Argentina. The objective was to update the information on the epidemiology of rabies variant 4 and to analyze the effectiveness of the control measures usually recommended by health services. The review carried out shows only 5 notifications in South America corresponding to canines and felines between 2009 and 2019 and with regard to people, three cases were reported: in Chile in 1963 and 2013 and in Colombia in 2012. The identification of insectivorous bats carrying rabies ranges from 4% to 15%. For its part, the veterinary public health service of the Health Ministry of Rio Negro collected insectivorous bats from passive surveillance activities. The bats were sent to the Laboratory of the Luis Pasteur Institute in the city of Buenos Aires for identification of rabies virus. A total of 294 insectivorous bats were analyzed in 26 locations. The proportion of the infected ones was 14.6% (95% CI 9.5-17.8) although there were no cases in dogs, cats or people. Insectivorous bats can be a risk factor for canines, felines, and humans, although notifications of variant 4 cases in these species are extremely low in South America, so an evaluation of the recommended and applied control strategy seems to be required, so far, as it is not cost-effective, and involves increasing operating costs in financial and human resources, proposing more efficient risk control alternatives.